A new species of Paris (Melanthiaceae) from Yunnan, China - Liu, Yuyu; Luo, Dandan; Yao, Hui; Zhang, Xiaocan; Yang, Liwu; Duan, Baozhong (Phytotaxa, 2017)
Paris Linnaeus (Linnaeus 1753: 367) is the largest genus within Melanthiaceae, with more than 27 species (The Plant List 2013, Wang et al. 2017). It is widely distributed in the regions of southwestern China, especially Yunnan, Guizhou and other plateau provinces (Li 1998, Wu et al. 2004, Zhang et al. 2007, Huang et al. 2012). The genus Paris has 22 species in China, of which 14 are distributed in Yunnan (Li 1998) and five species are endemic to Yunnan; therefore, their species diversity ranks first in China (Zhao et al. 2016). Most species of Paris with a thick rhizome have been widely used in China for a long time to treat tumors, chronic bronchitis, for traumatic injuries, and as antimicrobial agent, achieving significant effect (Wu et al. 2004).